A novel simulator-based checklist for evaluating residents' competence in cerebral angiography in China - Yi, Xuxia; Wang, Gang; Zhang, Nai; Si, Weixin; Lv, Jianping (Frontiers in Neurology, 2023)
Background Nowadays, with the fast-increasing demand for neuro-endovascular therapy, surgeons in this field are in urgent need. Unfortunately, there is still no formal skill assessment in neuro-endovascular therapy in China. Methods We used a Delphi method to design a newly objective checklist for standards of cerebrovascular angiography in China and evaluated its validity and reliability. A total of 19 neuro-residents with no interventional experience and 19 neuro-endovascular surgeons from two centers (Guangzhou and Tianjin) were recruited; they were divided into two groups: residents and surgeons. Residents completed a simulation-based cerebrovascular angiography operation training before assessment. Assessments were under live and video record forms with two tools: the existing global rating scale (GRS) of endovascular performance and the new checklist. Results The average scores of residents were significantly increased after training in two centers (p < 0.05). There is good consistency between GRS and the checklist (p = 0.856). Intra-rater reliability (Spearman's rho) of the checklist was >0.9, and the same result was also observed in raters between different centers and different assessment forms (p < 0.001, rho > 0.9). The reliability of the checklist was higher than that of the GRS (Kendall's harmonious coefficient is 0.849, while GRS is 0.684). Conclusion The newly developed checklist appears reliable and valid for evaluating the technical performance of cerebral angiography and differentiating between trained and untrained trainees' performance well. For its efficiency, our method has been proven to be a feasible tool for resident angiography examination in certification nationwide.